Progressive emergence of an oseltamivir‐resistant A(H3N2) virus over two courses of oseltamivir treatment in an immunocompromised paediatric patient. Issue 6 (29th March 2013) - Hurt, Aeron C.; Leang, Sook Kwan; Tiedemann, Karin; Butler, Jeff; Mechinaud, Francoise; Kelso, Anne; Downie, Peter; Barr, Ian G.
<x xml:space="preserve">Abstract</x> A minor viral population of oseltamivir‐resistant A(H3N2) viruses (E119V neuraminidase mutation) was selected and maintained in a continually infected immunocompromised child following initial oseltamivir treatment. A subsequent course of oseltamivir given 7 weeks later rapidly selected for the E119V variant resulting in a near‐pure population of the resistant virus. The study highlights the challenges of oseltamivir treatment of immunocompromised patients that are continually shedding virus and demonstrates the ability of the E119V oseltamivir‐resistant virus to be maintained for prolonged periods even in the absence of drug‐selective pressure.